2019
DOI: 10.1515/ijamh-2019-0121
|View full text |Cite
|
Sign up to set email alerts
|

The effect of life skills training with health literacy strategies on self-esteem and self-efficacy in female students during puberty

Abstract: Background Puberty is a sensitive period of life for developing specific skills and knowledge and acquiring abilities and attributes that are essential for managing emotions and assuming adult roles. Thus, this has implications for health educational programs to responses to the experimentation and exploration that takes place during puberty. Objectives This study aimed to examine the effect of life skills training using health literacy strategies on self-esteem and self-efficacy in adolescent female student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…According to the participants, poor parenting skills and poor performance in premarital counseling have also caused a great deal of tension and stress in Iran. In confirmation of our findings, other studies indicate that many people cannot solve the problems they face due to lifestyle changes, modernism, and cultural changes (28). Many mental health issues and psychosocial problems are associated with life skills (29,30).…”
Section: Discussionsupporting
confidence: 87%
“…According to the participants, poor parenting skills and poor performance in premarital counseling have also caused a great deal of tension and stress in Iran. In confirmation of our findings, other studies indicate that many people cannot solve the problems they face due to lifestyle changes, modernism, and cultural changes (28). Many mental health issues and psychosocial problems are associated with life skills (29,30).…”
Section: Discussionsupporting
confidence: 87%
“…However, a universal CBT trial in Swedish primary schools found no evidence of long-term effects of such program on anxiety prevention [ 71 ]. Five intervention studies based on life-skill-training were found to be effective in promoting self-efficacy [ 72 , 73 ], self-esteem [ 73 , 74 ], and reducing depression/anxiety-like symptoms [ 72 , 75 , 76 ]. Courses covering stress management skills have also been reported to improve life satisfaction, increase happiness and decrease anxiety levels among students in developing countries [ 77 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that both methods are equally effective (22). In Jafarigiv and Peyman's study in 2019 on the effect of life skill training using self-esteem and self-e cacy literacy strategies, participants' scores of both and self-e cacy were signi cantly improved after the intervention (23). The study of Xia and colleagues showed that positive family atmosphere and e cient parenting leads to better problem-solving skills and less violent behaviors among adolescents.…”
Section: Discussionmentioning
confidence: 98%